1986
DOI: 10.1210/endo-119-1-236
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Release of Luteinizing Hormone by Rat Anterior Pituitary Cells: Effects of Cytochalasins B and D*

Abstract: We determined the role of microfilaments in regulating LH synthesis (translation or glycosylation) and release from cultured rat anterior pituitary cells under basal and GnRH-stimulated conditions. Cells were pretreated for 2 h with microfilament-disrupting drugs, cytochalasin B (CB; 2 and 20 microM) or cytochalasin D (CD; 1 and 10 microM). LH synthesis and release were measured after 4 h of incubation with or without 1 nM GnRH and drugs. LH translation and glycosylation were monitored by measuring the incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…We also found that both AA and melittin preferentially released stored IR-LH,whereas GnRH released both stored and newly glycosylated and translated LH. These findings support our previous observations [42] that release o f stored LH appears to be regulated independently of newly syn thesized LH.…”
Section: Measurements O F Uptake O F Labeled Precursors and Incorporasupporting
confidence: 92%
“…We also found that both AA and melittin preferentially released stored IR-LH,whereas GnRH released both stored and newly glycosylated and translated LH. These findings support our previous observations [42] that release o f stored LH appears to be regulated independently of newly syn thesized LH.…”
Section: Measurements O F Uptake O F Labeled Precursors and Incorporasupporting
confidence: 92%
“…Values are means + or S.E.M. and the effect of cytochalasin has been investigated (Liu & Jackson 1986). However, only a few reports have shown changes in the cytoskeletons of pituitary cells during cell excitation (van de Moortele et al 1991, Kiley et al 1992, Carbajal & Vitale 1997.…”
Section: Discussionmentioning
confidence: 99%
“…The goals of the first experiment were 1) to establish that male pituitary cells cultured under the present conditions remained functionally viable, as measured by incorporation of 35 S-Met and 3 H-Gln into total protein as a function of time, and 2) to determine the effects of continuous exposure to GnRH for various periods of time on LH release and radiolabeled precursor incorporation into immunoprecipitable LH subunits. Pituitary cells, cultured for 4 days in AMEM containing 10% CHS, were preincubated for 1 h in 10 ml glucosamine-and methionine-free Krebs-Ringer-I bicarbonate buffer (KRB-I) to reduce the endogenous pool of synthetic precursors.…”
Section: Explmentioning
confidence: 99%
“…Pituitary cells, cultured for 4 days in AMEM containing 10% CHS, were preincubated for 1 h in 10 ml glucosamine-and methionine-free Krebs-Ringer-I bicarbonate buffer (KRB-I) to reduce the endogenous pool of synthetic precursors. The cells were then transferred to 1.5-cm (diameter) culture dishes containing 1.0 ml KRB-I, 30 fid 3 H-Gln (43 Ci/mmol), and 15 /iCi 35 S-Met (1116 Ci/mmol), with or without 1 nM GnRH. The cells were incubated for 2, 4, 6, 8, or 12 h at 37 C under a humidified air-CO 2 mixture.…”
Section: Explmentioning
confidence: 99%
See 1 more Smart Citation